2019
DOI: 10.1590/1678-4162-10478
|View full text |Cite
|
Sign up to set email alerts
|

Influência da dificuldade de inseminação, temperamento e cortisol plasmático sobre a taxa de concepção de vacas e novilhas da raça Nelore inseminadas em tempo fixo

Abstract: RESUMO O objetivo do presente experimento foi avaliar efeito do estresse e da dificuldade de inseminação (DifIA) sobre a taxa de concepção (TC) de vacas (n=93) e novilhas (n= 72) Nelore submetidas à IATF. No D9, anotou-se nota de temperamento (NTe) e tempo da saída do brete (TSB) de todos os animais e coletou-se sangue das novilhas. No dia da IATF (D11), anotou-se NTe, TSB, DifIA e tempo de IA. A TC foi 36% para vacas e 46% para novilhas (P>0,05). Não foi observado efeito de Nte sobre TC (P>0,05). Porém,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…According to Oliveira et al (2019) stress parameters such as insemination difficulty and temperament did not influence cows and heifers submitted to FTAI, a result similar to that observed in this study. However, according to the authors, the lower fertility in the FTAI was suggested in animals in which greater difficulty and/or time needed to complete the AI was observed.…”
Section: Discusionsupporting
confidence: 89%
See 2 more Smart Citations
“…According to Oliveira et al (2019) stress parameters such as insemination difficulty and temperament did not influence cows and heifers submitted to FTAI, a result similar to that observed in this study. However, according to the authors, the lower fertility in the FTAI was suggested in animals in which greater difficulty and/or time needed to complete the AI was observed.…”
Section: Discusionsupporting
confidence: 89%
“…Insemination difficulty (ID) was assessed by the technician while performing the management, attributing a score from 1 to 3 (1 = low difficulty and 3 high difficulty) to the animal according to its difficulty in performing the cervix transposition technique (Oliveira et al 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation